Rehabilitating Social Systems Through the Sekolah Perjumpaan Praxis Model - Miftahul Arifin (Universitas Muhammadiyah Sidoarjo, 2025)
(General Background) Contemporary Indonesian education often prioritizes cognitive achievement while neglecting moral and social integrity, leading to weakened communal values and fragmented social systems. (Specific Background) Traditional character education approaches remain individualistic and exam-oriented, offering limited strategies for cultivating honesty, tolerance, and empathy through social praxis. (Knowledge Gap) Although speech act theory conceptualizes language as action, it largely lacks practical application in community-based moral education within heterogeneous societies. (Aims) This study explores how speech act theory, integrated with social systems theory, can be operationalized through Sekolah Perjumpaan, a community-based model designed to rehabilitate social relations and foster collective character. (Results) Using qualitative case study methods—interviews, observations, and document analysis—the study found that Sekolah Perjumpaan aligns intentional states (thinking, feeling, desiring, willing) with speech acts (assertive, expressive, directive, commissive) to form sustained moral habits and social cohesion. (Novelty) The research introduces M. Husni Muadz’s innovative praxis that transforms speech act theory from abstract philosophy into an actionable pedagogical framework grounded in Indonesian socio-cultural contexts. (Implications) The findings position Sekolah Perjumpaan as a replicable model for community-based character education and social system rehabilitation, offering both theoretical advancement and policy relevance for national education reform. Highlights: Integrates speech act theory with social systems for moral education. Transforms language use into a tool for social rehabilitation. Offers a replicable community-based model for character development. Keywords: Speech Act Theory, Character Education, Social Systems, Community Learning, Sekolah Perjumpaan